Indicators of reaching the expectations of the industrial project in the Manaus Free Trade Zone from the process of monitoring mandatory counterparts (Research, Society and Development, 2022)
Assuming that any waiver of revenue to the treasury needs to be duly substantiated and justified, as it is a potential public resource not collected for a pre-established purpose, it is important to understand how the concession process, implementation and monitoring of the promoted projects takes place. Decree-law No. 288/1967 states that, in order to be entitled to tax benefits, it is necessary to have a project approved by the Board of Directors of Suframa (CAS) and to comply with the counterparts established in that regulatory framework. After approval of the industrial project, the company holding the Approval Act must comply with its implementation within a period of up to 36 months. Once the project is implemented, it is monitored by the Manaus Free Zone Superintendence (SUFRAMA), thus concluding the cycle of waiver granted: if the assumptions presented in the industrial project are met, the company continues with the tax benefits; if, on the contrary, the company does not comply with the established, and after rights of defense - full defense and contradictory - does not comply with what had been established, the Federal Revenue of Brazil is informed so that the tax credit is released and the taxes due are collected. . The study in question details the process of granting, implementing and monitoring the industrial project and, based on the data collected resulting from the sample selected between the years 2017 to 2020, built indicators for reaching the expectations of the approved industrial project that structured the flow of inspection and analysis of the results of the tax waiver granted.